rdlc 2021
DOI: 10.7764/rdlc.20.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on punching shear strength of concrete slabs containing sintered fly ash aggregates

Abstract: This paper presents experimental and numerical investigations on M30 Grade of concrete containing 40% of sintered fly ash aggregates (SFAs) on the punching behaviour of reinforced concrete (RC) slabs. Two 1000 x 1000 x 100 mm reinforced concrete slabs were cast and subjected to punching tests. The experimental results were compared with creating a nonlinear finite element programme using ABAQUS. This 3D Finite element analyses were performed with the appropriate modelling of element size and the constitutive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Impact loads are severely intense and could occur within nanoseconds due to collisions, explosions, falling heavy objects, and earthquakes or waves affecting offshore structures [1][2][3][5][6][7]11,12,21,[23][24][25]27,28,81]. Structural responses to the impact load are categorized into impulsive, dynamic, and quasi-static loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact loads are severely intense and could occur within nanoseconds due to collisions, explosions, falling heavy objects, and earthquakes or waves affecting offshore structures [1][2][3][5][6][7]11,12,21,[23][24][25]27,28,81]. Structural responses to the impact load are categorized into impulsive, dynamic, and quasi-static loading.…”
Section: Discussionmentioning
confidence: 99%
“…Impact loads are severely intense in nature and could occur within nanoseconds as the result of collisions, explosions, falling heavy objects, earthquakes, or wave effects on offshore structures [1][2][3][5][6][7][8]11,12,21,[24][25][26][27][28]. Structural responses to impact loads are categorized into three sections: (i) impulsive loading, where the impact duration ends before the structure reaches its maximum response; (ii) dynamic loading, where the structure reaches its maximum response almost simultaneously with the end of the impact duration; (iii) quasi-static loading, where the structure reaches its maximum response before the end of the impact duration.…”
Section: Rc Slab Behaviors Under Impact Loadsmentioning
confidence: 99%
“…Concrete production using cold bonded and sintered fly ash aggregates, concluded the sintered fly ash aggregates had a better mechanical properties and higher durability factors (Güneyisi, E, Gesoğlu, M, Pürsünlü & Mermerdaş, 2013). The punching shear strength on reinforced concrete slabs using combined natural and clay aggregates, shows that the incorporation of rounded aggregates in concrete possess less punching angle compared to natural aggregate concrete and the study concluded that the round shape of aggregates provides higher restriction to punching (Youm, Kim, Moon, 2014& Babu B, R, 2021.…”
Section: Introductionmentioning
confidence: 93%
“…Programs like ANSYS, LUSAS, and ABAQUS help to identify the deformation zones and stress values of the samples. The finite element approach of the ANSYS program was used to identify the deformation zones in the beam in this study [38].…”
Section: Introductionmentioning
confidence: 99%